2021
DOI: 10.3389/fneur.2021.630435
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Monitoring of the Effect of Botulinum Toxin A on Paretic Calf Muscles of Children With Cerebral Palsy With MRI: A Preliminary Study

Abstract: Background: Muscles from patients with cerebral palsy (CP) are often spastic and form contractures that limit the range of motion. Injections of botulinum toxin A (BTX) into the calf muscles are an important treatment for functional equinus; however, improvement in gait function is not always achieved. BTX is also used to test muscle weakening for risk evaluation of muscle lengthening surgery. Our aim was to assess the effect of BTX over time on calf muscle properties in pediatric CP patients with MRI.Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…A recent study evaluating the possible degenerative effect of BoNT-A on calf muscles in CP-affected children supports our statement thanks to an MRI examination of MG and SOL that corroborates the hypothesis of a non-significant role of BoNT-A in determining a meaningful fibroadipose infiltration [26].…”
Section: Discussionsupporting
confidence: 88%
“…A recent study evaluating the possible degenerative effect of BoNT-A on calf muscles in CP-affected children supports our statement thanks to an MRI examination of MG and SOL that corroborates the hypothesis of a non-significant role of BoNT-A in determining a meaningful fibroadipose infiltration [26].…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, the ankle plantarflexors are shortened during toe-walking and present, therefore, a reduced force-generating capacity ( Herman and Bragin, 1967 ; Hoy et al, 1990 ; Perry et al, 2003 ). Patients with spasticity, prolonged equinus postures, and/or fixed muscular contractures may also present alteration of the underlying muscle morphology and intrinsic mechanical properties ( Tardieu et al, 1982 ; Delp, 2003 ; Weidensteiner et al, 2021 ), even though it was shown that children with diplegic CP were able to generate maximum ankle torques at similar joint angles ( Engsberg et al, 2000 ; Neptune et al, 2007 ). Therefore, restoring a more optimal foot and ankle position, as during heel-to-toe gait, may lead to improvements in muscle functionality and strength.…”
Section: Discussionmentioning
confidence: 99%
“…Although toe walking is frequently observed in children with and without cerebral palsy, the exact underlying mechanism is unknown. It is, however, understood that muscles from CP patients can be spastic and form contractures, which limit the range of motion [32]. This is often seen specifically in the calf muscles, which can lead to toe walking.…”
Section: Discussionmentioning
confidence: 99%
“…An effective, yet temporary treatment option for toe-walking patients with CP and spastic diplegia is Botulinum toxin A, or Botox injections. Botox can be injected into the bilateral calf muscles to promote functional equinus, control spasticity, and improve gait function [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation